The fetal fibronectin test is superior to cervical length measurement in predicting preterm birth in twin pregnancies: a retrospective observational study. (April 2020) - Holzer, Iris; Koch-Trappel, Markus; Leitich, Harald; Meyer, Elias Laurin; Farr, Alex; Helmer, Hanns
Abstract: Objectives: Twin pregnancies have a higher likelihood to experience spontaneous preterm birth (PTB). Those with imminent PTB need to be determined in order to undergo fetal lung maturation with glucocorticoids and therewith improve neonatal outcomes. The aim of this study was to assess the predictive value of the fetal fibronectin (fFN) test and the measurement of cervical length in twin pregnancies with symptoms of imminent PTB. Study design: We performed an observational study on all twin pregnancies at the Medical University Vienna. Women were admitted to the hospital either due to symptoms of imminent PTB or due to a shortening of the cervical length before completed 34 weeks of gestational age. Logistic regression analysis was performed to assess the predictive value of the fFN test and cervical length on imminent preterm birth. Results: The data of 82 women with twin pregnancies were eligible, of which 10 (12 %) had a positive, 45 (55 %) a negative, 21 (26 %) an unclear fFN result, and 6 (7 %) showed missing data. Cervical length ≤20 mm did not show any statistical significant prediction of PTB in our study cohort. After 7 days, 4/10 (40 %) pregnant women with positive fFN test gave birth, while 4/45 (9 %) women with a negative fFN test gave birth. Within 14 days after hospitalization, 6/10 (60 %) women with a positive fFN test gave birth, compared to 4/45 (9 %) with a negative fFN test. The positive fFN test was a statistically significant predictor of PTB within 7 days ( p = 0.02) and 14 days ( p = 0.004), respectively. Conclusion: The fFN test has the potential to detect women with twin pregnancies, who are at risk of giving birth within the following days. Hence, the practice of hospitalizing women solely due to the shortening of the cervical length cannot be supported.